APPLICATION OF NUMBERED HEADS TOGETHER (NHT) TYPE COOPERATIVE LEARNING MODELS WITH UNO CARD MEDIA TO IMPROVE MATHEMATICS LEARNING RESULTS - Fitri, Ayu; Nur DS, Yulistina; Fauzi, Mochamad (International Journal of Psychosocial Rehabilitation, 2020)
This research is motivated by students having difficulty in solving questions about the material operations of counting numbers, students ashamed and not confident to come to the front of the class to fill in the questions. This study aims to describe the implementation of learning and learning outcomes in mathematics. This research uses Classroom Action Research (CAR) with two cycles. Based on research data obtained satisfactory results. This can be seen classical completeness increases in cycle I to 63% with an average of 73, then a significant increase in cycle II to 83% with an average of 80. Students who are shy and have no confidence, become eager to learn and move forward. . This shows that the application of cooperative learning models with uno card media can improve mathematics learning outcomes.